Microbial Metazoa Are Microbes Too - Holly M. Bik (American Society for Microbiology, 2019)
ABSTRACT Microbial metazoa inhabit a certain “Goldilocks zone,” where conditions are just right for the continued ignorance of these taxa. These microscopic animal species have body sizes of <1 mm and include diverse groups such as nematodes, tardigrades, kinorhynchs, loriciferans, and platyhelminths. The majority of species are too large to be considered in single-cell genomics approaches, yet too small to be wrapped into international genome sequencing initiatives. Other microbial eukaryote groups (namely the fungal and protist communities) have gained significant momentum in recent years, driven by a strong community of researchers united behind a common goal of culturing and sequencing new representatives. However, due to historical factors and difficult taxonomy, persistent research silos still exist for most microbial metazoan groups, and public molecular databases remain sparsely populated. Here, I argue that small metazoa should be embraced as a key component of microbial ecology studies, promoting a holistic and cutting-edge view of natural ecosystems.